Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Digital Berbantuan AI dalam Pemahaman Konsep Matematika Siswa SMP - Hukma Gaffar; Ernawati; A. Muhajir Nasir (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study aims to develop an artificial intelligence (AI)–assisted digital Student Worksheet (LKPD) to improve junior high school students’ understanding of mathematical concepts on fraction material. The development followed the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The resulting product is a web-based worksheet accessible via QR code, equipped with animations, videos, interactive images, and an AI chatbot as a virtual tutor. Validation by material experts and media experts produced an average score of 88.2%, categorized as highly valid. A limited trial involving 20 seventh-grade students showed an improvement in learning outcomes with an N-Gain score of 0.65 (medium–high category). Students’ responses to the digital worksheet were also highly positive, with an average score of 3.56 across the aspects of attractiveness, ease of use, clarity of material, and usefulness of AI features. These findings indicate that the AI-assisted digital worksheet is feasible and effective as an innovative learning medium to enhance motivation and conceptual understanding of mathematics among junior high school students.